(3GdJShjb GdUfGYj (B/s - (3GdUejOYj, eMehO LGSes; (3YKeGf, jhSa QOjfI s ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2011)
(3WHjYI GdJShjb GdUfGYj h JLRFI GdShb GdUfGYjI , CfhGY GdefJLGJ GdUfGYjI h Sdhc GdeTJQj GdUfGYj , GdefJL GdUfGYj h JSYjQh JQhjL GdefJLGJ GdUfGYjI , CfXeI GdGeOGO GdUfGYj h CNjQG fXe GdeYdheGJ GdJShjb GdUfGYjs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb(B- (3GdUfGYIs